Performance of [18F]flutemetamol amyloid imaging against the neuritic plaque component of CERAD and the current (2012) NIA‐AA recommendations for the neuropathologic diagnosis of Alzheimer's disease. Issue 1 (1st July 2017) - Salloway, Stephen; Gamez, Jose E.; Singh, Upinder; Sadowsky, Carl H.; Villena, Teresa; Sabbagh, Marwan N.; Beach, Thomas G.; Duara, Ranjan; Fleisher, Adam S.; Frey, Kirk A.; Walker, Zuzana; Hunjan, Arvinder; et al.
Abstract: Introduction: Performance of the amyloid tracer [ 18 F]flutemetamol was evaluated against three pathology standard of truth (SoT) measures including neuritic plaques (CERAD "original" and "modified" and the amyloid component of the 2012 NIA‐AA guidelines). Methods: After [ 18 F]flutemetamol imaging, 106 end‐of‐life patients who died underwent postmortem brain examination for amyloid plaque load. Blinded positron emission tomography scan interpretations by five independent electronically trained readers were compared with pathology measures. Results: By SoT, sensitivity and specificity of majority image interpretations were, respectively, 91.9% and 87.5% with "original CERAD, " 90.8% and 90.0% with "modified CERAD, " and 85.7% and 100% with the 2012 NIA‐AA criteria. Discussion: The high accuracy of either CERAD criteria suggests that [ 18 F]flutemetamol predominantly reflects neuritic amyloid plaque density. However, the use of CERAD criteria as the SoT can result in some false‐positive results because of the presence of diffuse plaques, which are accounted for when the positron emission tomography read is compared with the 2012 NIA‐AA criteria. Highlights: Determination of the accuracy of [ 18 F]flutemetamol image read against Aβ at autopsy. High sensitivity and specificity to 3 neuropathologic criteria as Standards of Truth. Images are 100% specific when the SoT reflects both neuritic and diffuse plaques. This study has the largest autopsy validation cohort for Aβ PET tracers to date.